Ten Tips to Hurdle the Injuries and Illnesses During Major Athletics Championships: Practical Recommendations and Resources - Edouard, Pascal; Richardson, Andy; Murray, Andrew; Duncan, Jennifer; Glover, Danny; Kiss, Marianna; Depiesse, Frédéric; Branco, Pedro (Frontiers in Sports and Active Living, 2019)
Participating or winning a medal in major track and field (athletics) competitions is the goal of every athlete. However, health problems can impair sports performance and affect this dream. Therefore, we present ten tips to help hurdle the challenges of illness/injury at major athletics championships: (1) Prepare for travel (medical checking, vaccine, time-zone, jet lag, culture, food habits…), (2) Respect athlete characteristics and discipline specificity (sex, endurance/explosive), (3) Educate athletes and their entourages regarding prevention, (4) Vigilance of painful symptoms and subclinical illness markers, (5) Avoid infection risk (washing hands, safe food and drink, avoid contact with sick people…), (6) Train appropriately and optimally (physical conditioning, technical training, load management, and psychological preparation), (7) Health status (history of previous injuries, well-being in the month before championships), (8) Lifestyle (good sleep, regular hydration and nutrition with safe water/food, regular fruits and vegetables, improve recovery strategies…), (9) Environmental considerations (heat, cold, air cleaning, changes or climatic conditions…), (10) Safety (equipment, rules, own-practice in athletics, and extra-sport activities). These ten tips “PREVATHLES” are based on our field experience in addition to existing epidemiological and experimental literature in athletics and other sports. Although there is currently no scientific evidence for their efficacy, sound judgement, and logical practice provide a strong basis, and given the low risk of using them in the benefit/risk balance, we suggest athletes and those around them follow these ten tips to limit the impact of injury/illness on championship performance.